The Effectiveness of Madrasah Management in Improving Madrasah Quality - Saila Rachmawati (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
The world of Pesantren is always interesting and there is no end to it to be discussed and discussed. Because in it there are many uniqueness that cannot be found in other educational institutions besides pesantren. The pesantren referred to here is the kholafi pesantren (pesantren which contains religious knowledge as well as general knowledge). In this modern era, most parents prefer to entrust and send their children to educational institutions that have and pay attention to religious content. The concerns that arise must also be balanced with the awareness of massive changes taking place. So that individuals who live and experience shifting demands of the present do not take a wrong step in responding to all the changes that exist. The development of educational institutions is inseparable from the role of the leader in control of an educational institution. This research has the aim that the founders of madrasah or Islamic boarding schools can adopt the methods or strategies of other pesantren so that they can continue to exist in the midst of this millennial era. This research uses qualitative research methods, namely by collecting data, documents and interviews with several sources. The method used in this research is a qualitative approach, namely research where information is obtained by describing the existing phenomena. The data collection techniques used observation, interviews, and documents.